2014
DOI: 10.18632/oncotarget.1917
|View full text |Cite
|
Sign up to set email alerts
|

Heat shock protein 27 regulates human prostate cancer cell motility and metastatic progression

Abstract: Prostate cancer (PCa) is the most common form of cancer in American men. Mortality from PCa is caused by the movement of cancer cells from the primary organ to form metastatic tumors at distant sites. Heat shock protein 27 (HSP27) is known to increase human PCa cell invasion and its overexpression is associated with metastatic disease. The role of HSP27 in driving PCa cell movement from the prostate to distant metastatic sites is unknown. Increased HSP27 expression increased metastasis as well as primary tumor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
35
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 52 publications
(39 citation statements)
references
References 42 publications
3
35
0
1
Order By: Relevance
“…The cause of that outcome may be closely related to tissue-specific expression. HSP27 has been reported to be overexpressed and associated with poor prognosis in many human cancers, including breast, rectal, gastric, lung, liver and prostate cancers (33)(34)(35)(36). Contrary to the findings in most cancers, in human esophageal squamous cell carcinoma (HESCC), the expression of HSP27 was low, and this low expression was correlated with poor prognosis (37,38).…”
Section: Discussionmentioning
confidence: 96%
“…The cause of that outcome may be closely related to tissue-specific expression. HSP27 has been reported to be overexpressed and associated with poor prognosis in many human cancers, including breast, rectal, gastric, lung, liver and prostate cancers (33)(34)(35)(36). Contrary to the findings in most cancers, in human esophageal squamous cell carcinoma (HESCC), the expression of HSP27 was low, and this low expression was correlated with poor prognosis (37,38).…”
Section: Discussionmentioning
confidence: 96%
“…The importance of angiogenesis and lymphangiogenesis in cancer development is fundamental, since tumour growth and metastasis primarily depend on the formation of new vessels (Hanahan and Weinberg 2011). HSPB1 increases cancer cell motility, and its overexpression and phosphorylation are associated with increased metastatic and invasive potential of cells both in vivo and in vitro in various cancer types (Gibert et al 2012;Voll et al 2014;Yang et al 2010). Moreover, alpha-crystallins play an important role in cell motility and invasion.…”
Section: Shsps In Cancermentioning
confidence: 99%
“…In human hepatocellular carcinoma, HSPB1 stimulates tumor progression through facilitating the hepatocellular carcinoma cells metastasis via Akt signaling [6,22]. Both in vivo and in vitro studies of the prostate cancer indicated that HSPB1 regulates human prostate cancer cell motility and metastatic progression via increased the expression of matrix metalloproteinase 2 (MMP-2) [29], which is a key stimulator for cancer cell invasion [33]. In mouse lung cancer development, HSPB1 was proved to induce the lung cancer cells proliferation via activator protein-1 (AP-1) dependent pathway [7].…”
Section: Resultsmentioning
confidence: 99%